Mengembangkan Pengetahuan Metakognisi Anak Usia Dini di PG/TK Melalui Evaluasi Kegiatan Cerita-Rencana-Evaluasi dan Diskusi Hasil Karya [Improving Metacognition Knowledge in Early Childhood in PG/TK Using Evaluation of Story-Plan-Review and Portfolio Discussion] - Indah Novebrita (Jurnal Teropong Pendidikan, 2021)
Metacognition skill is important for every individual to be able to understand their own way of thinking and to choose the most appropriate strategy for himself. Stimulation to develop metacognition skills in early childhood can be done through routine (Story-Plan-Review and Portfolio Discussion) which is a series of activities consisting of Metacognition components performed by children every day. This routine makes the children being trained to be able to think about how they think automatically because of habit factors. The result of metacognition knowledge assessment shows that 90% of respondents were able to identify things that they consider can facilitate themselves in doing a task, while 87% of respondents were able to identify the things that they perceive can complicate themselves in finishing a task. 87% of respondents can also explain that they have chosen to do things that they consider can make it easier and try to avoid or find a way out to deal with difficult things when completing a task. 12 students who are able to answer 9 questions from 10 questions asked by researcher about metacognition knowledge are the students that present at least 88% of total effective days in academic year. From the findings above it can be concluded that metacognition can be developed in early childhood through routine activities.